Structural Basis for Unusual TCR CDR3β Usage Against an Immunodominant HIV-1 Gag Protein Peptide Restricted to an HLA-B*81:01 Molecule - Liu, Yang; Lei, Jun; San, Dan; Yang, Yi; Paek, Chonil; Xia, Zixiong; Chen, Yongshun; Yin, Lei (Frontiers in Immunology, 2022)
In HIV infection, some closely associated human leukocyte antigen (HLA) alleles are correlated with distinct clinical outcomes although presenting the same HIV epitopes. The mechanism that underpins this observation is still unknown, but may be due to the essential features of HLA alleles or T cell receptors (TCR). In this study, we investigate how T18A TCR, which is beneficial for a long-term control of HIV in clinic, recognizes immunodominant Gag epitope TL9 (TPQDLTML180-188) from HIV in the context of the antigen presenting molecule HLA-B*81:01. We found that T18A TCR exhibits differing recognition for TL9 restricted by HLA-B*08:01. Further, via structural and biophysical approaches, we observed that TL9 complexes with HLA-B*08:01 undergoes no conformational change after TCR engagement. Remarkably, the CDR3β in T18A complexes doesn't contact with TL9 at all but with intensive contacts to HLA-B*08:01. Instead CDR2β is adopted with moderate contacts to TL9 for the compensation, which suggests the compromised focus on the TL9 peptide by the T18A TCR. In consistent with that, the binding kinetic data of T18A TCR revealed that this TCR can recognize TL9 epitope and several mutant versions effectively which might explain the correlation of T18A TCR with better clinic outcomes despite the relative high mutation rate of HIV. Collectively, we provided a portrait of how CD8+ T cells engage in HIV-mediated T cell response.